Innowacyjny nauczyciel, czyli kto? Próba definicji pojęcia - Półtorak, Ewa; Gałan, Beata (Neofilolog, 2019)
Innovativeness constitutes one of the core elements of modern ducation development. The phenomenon in question can be analysed in the context of the actions taken by each of the participants of the learning/teaching process. The paper is focused mostly on the teacher’s activity. On the basis of an empirical study, the Authors aim at defining the notion of an innovative teacher, and, more specifically, a language teacher.